2016
DOI: 10.1186/s12951-016-0221-x
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced effects of m-tetrahydroxyphenylchlorin loaded lipid nanoemulsions on multicellular tumor spheroids

Abstract: BackgroundPhotosensitizers are used in photodynamic therapy (PDT) to destruct tumor cells, however, their limited solubility and specificity hampers routine use, which may be overcome by encapsulation. Several promising novel nanoparticulate drug carriers including liposomes, polymeric nanoparticles, metallic nanoparticles and lipid nanocomposites have been developed. However, many of them contain components that would not meet safety standards of regulatory bodies and due to difficulties of the manufacturing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 38 publications
(51 reference statements)
4
26
0
Order By: Relevance
“…20 For example, 50 nm-sized lipid NPs showed a considerably deeper penetration and homogeneous distribution as compared to 120 nm-sized ones. 76 NPs .100 nm are too large to cross ECM interstitial spaces in spheroid 73,77 and are confined to the outer layers as demonstrated with gelatin NPs (210 nm) that only penetrated ~40 µm deep. 20 Micelles are generally smaller than liposomes and penetrate deeply and …”
Section: Impact Of Physicochemical Properties Of Nps On Their Penetramentioning
confidence: 99%
“…20 For example, 50 nm-sized lipid NPs showed a considerably deeper penetration and homogeneous distribution as compared to 120 nm-sized ones. 76 NPs .100 nm are too large to cross ECM interstitial spaces in spheroid 73,77 and are confined to the outer layers as demonstrated with gelatin NPs (210 nm) that only penetrated ~40 µm deep. 20 Micelles are generally smaller than liposomes and penetrate deeply and …”
Section: Impact Of Physicochemical Properties Of Nps On Their Penetramentioning
confidence: 99%
“…plates, hanging drop methods etc.) where they assume naturally a spherical aggregate conformation [67][68][69] or by embedding cells in a 3D matrix. The closely packed arrangement where cell to cell contact is dominant and the reduced rate of diffusion of drugs and oxygen through the spheroids makes them comparable to in vivo tissues.…”
Section: Spheroidsmentioning
confidence: 99%
“…In a similar approach in our former studies we presented the successful encapsulation of mTHPC into fully biocompatible and biodegradable lipid nanoemulsions and showed first data in monolayer cells [ 23 , 24 ]. In our subsequent investigations in multicellular tumor spheroids we identified a formulation with a high mTHPC payload that featured the same excellent PDT effects as the free mTHPC but with a reduced dark toxicity (Lipidots) [ 25 ]. This nanoemulsion consists of a phospholipid (lecithin) monolayer, protected by a PEG-shell with a soybean/wax core, where mTHPC is incorporated.…”
Section: Discussionmentioning
confidence: 99%
“…We recently developed a biocompatible nanoemulsion (Lipidots) [ 23 ] as carrier for mTHPC with excellent optical properties which we subsequently tested in two in vitro studies [ 24 , 25 ]. It could be demonstrated that Lipidots can significantly lower the dark toxicity of mTHPC while maintaining its photodynamic activity.…”
Section: Introductionmentioning
confidence: 99%